Planning of Rigid Pavement Thickness in The Construction of The Sp. Door - Sp. Benakat Penungkal Regency Abab Lematang Ilir - Lilly Julian; Sartika Nisumanti; Khodijah Al Qubroh (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The access section to Benakat Village, Pali Regency is a special road made by the company, with the condition of the existing land being unpaved with a length of 1,375 meters and a width of 7 meters, and has severe damage triggered by vehicles with excess capacity or ODOL (Over Dimension Over Load)) that pass through that path. The purpose of this study was to determine the results of the calculation of rigid pavement thickness planning by comparing the 1993 AASHTO and 2017 MDPJ methods so that the road Sp. Doors – Sp. Benakat is able to accommodate ODOL vehicles. This study uses AASHTO 1993 and MDPJ 2017 as methods to produce rigid pavement thickness (Rigid Pavement) so that ODOL vehicles can pass. Based on the results of data analysis and calculations, the input indicators in each method are different for each method so that AASHTO 1993 produces a thickness of 35 cm, and in MDPJ it produces a thickness of 28.5 cm